A study into annulment (iqÄlah) from the perspective of Shiite jurisprudence and law - ÃšÂ¯Ã™Â„Ã˜Â¨Ã˜Â§Ã˜ÂºÃ›ÂŒ Ã™Â…Ã˜Â§Ã˜Â³Ã™ÂˆÃ™Â„Ã™Â‡, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â¬Ã˜Â¨Ã˜Â§Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Annulment is one of the institutions of contract cancellation in Shiite jurisprudence and law. One of the primary questions about every phenomenon is the question of the nature and character. Although traditionally Shiite jurists have held comparative and critical approaches toward the common views of Sunni jurists about the nature of annulment, they have not typically looked at the nature of contract annulment from the perspective of Shia jurisprudence. The present article explores the nature of âannulment of contractsâ as a legal and jurisprudential institution from the perspective of scholars of Shiite jurisprudence and law by observing their major views. Thus, the paper aims to review and investigate their opinions and provided reasons in order to clarify the strength of their hypotheses and theories regarding the nature of contract annulment.